Questões sociocientíficas: subsídios para uma ação didático-pedagógica em escolas em tempo integral - Silva, Brunno Inácio da (2020)
Research in Science Education has recently signaled the need for elements to encourage the formation of active and engaged citizens in our society. With the great advance of Science and Technology, it is also necessary a critical training to understand and experience the impact of these advances in society. In this sense, it is important to make use of strategies in science education that foster such discussions and, in this perspective, Socio-scientific Issues (QSC) appear as a methodological approach, considered as elements that provide greater reflection on the social role of science and its implications in science society. Currently, with the advancement of neoliberalism, we have several institutions that raise the banner of change in education. In Brazil, the Instituto de Corresponsabilidade pela Educação (ICE), is the organizationresponsible for raising this banner with full-time education. Therefore, this research aims to analyze the potential of the QSC approach in science teaching in full-time schools in the state of Rio Grande do Norte, from the perspective of the project's guiding documents and some teachers. For that, we used the IRAMUTEQ software as a research tool, which makes the Classificação Hierárquica Dependente (CHD), Análise Fatorial de Correspondências (AFC) and Word Cloud analyzes possible. To better understand the reality of teachers, a semi-structured interview was conducted with teachers from three schools’ full time. The results show several elements of the QSC, such as interdisciplinarity, the consideration for regional characteristics, the practices, and experiences in protagonist. We also identified the electives, the Life Project, the formation of values and the oriented study as subsidies for an educational didactic action in full-time schools. With that, we hope to contribute to teachers working in integral education and future teachers in this education system.